THE ANALYSIS OF LOCAL RESOURCES POTENTIAL TO IMPROVE WELFARE IN KUCUR VILLAGE, DAU SUB-DISTRICT, MALANG DISTRICT, EAST JAVA PROVINCE - Nasikh Nasikh; Mahirah Kamaludin; Mohd Al-Ikhsan Ghazali; Reniati Reniati (Fakultas Pertanian, Universitas Janabadra, 2019)
This study aims to analyze the local resources utilization to improve community’s welfare. This study employs qualitative research method by interviewing some informants who are chosen through purposive sampling in order to obtain some knowledge required by the researcher. The interview result and research finding are analyzed to identify the local resources in Kucur Village, Dau Sub district, Malang District Tourism Destination has been well-utilized and whether it brings significant effects to the local people. The research finding shows that the most potential local resources are water and natural scenery. The local resources have been utilized in the form of clean water distribution and tourism since 2005.